Islamic insurance: the tool of anticrisis managment? - S. Yu. Babenkova (Путеводитель предпринимателя)
This article describes the basic principles of Islamic insurance, its conceptual differences from the approaches used in the classical insurance, including in Russia. We considered and analyzed the prospects for the implementation and development of these tools in our country, including in the context of economic sanctions applied by a number of western countries.